Jurnalisme Publik pada Media Penyiaran Publik - Masduki Masduki; Bambang Muryanto (Jurnal Komunikasi, 2007)
Public journalism or civic journalism is a movement that has taken over the last ten years in the USA. Public journalism has emerged along side a revival of interest in civil society and civic participation by improving the quality of news coverage,for example by replacing coverage of political strategy with analysis of substantive issues. In public journalism, public can participate in defining their events. According to Broadcasting Law No. 32/2002, Radio of Republic Indonesia (RRI) and Television of Republic Indonesia (TVRI) has become public broadcasting. As a public broadcasting, the use of public journalism is necessary to move government oriented news to public oriented news in both stations's newsroom. Although, there are some conceptual and technical problems in RRI and TVRI, the successful coverage of Saturday's earthquake, May 27,2006 in Yogyakarta could be a lesson that have to be leraned develop amodelofpublicjoumalisminbothinstitutions.